2021
DOI: 10.1097/corr.0000000000001730
|View full text |Cite
|
Sign up to set email alerts
|

People Prefer to Continue with Painful Activities Even if They Lead to Earlier Surgery

Abstract: Background The degree to which physical activity results in arthritis progression is unknown, but it probably is less than most people believe. But the belief that painful activity is harmful has notable associations both with greater pain intensity and greater activity intolerance among people seeking care for painful conditions such as osteoarthritis. If there were evidence that people not seeking care would prefer to accommodate a painful cherished activity, even if such accommodation is harmful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 42 publications
0
16
1
Order By: Relevance
“…No demographics were collected from the participants. It has previously been shown that the AMT worker population is representative of the general United States internet population is similar studies[ 6 - 8 , 41 , 42 ]. However, the internet population may not be the same as the population treated for trigger finger.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…No demographics were collected from the participants. It has previously been shown that the AMT worker population is representative of the general United States internet population is similar studies[ 6 - 8 , 41 , 42 ]. However, the internet population may not be the same as the population treated for trigger finger.…”
Section: Discussionmentioning
confidence: 56%
“…Participants for this study were randomly recruited through AMT. Studies have shown that AMT produces results similar to conventional surveying techniques and the population surveyed is representative of the United States internet population[ 6 - 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, as Amiri et al [1] report in their recent study, “People Prefer to Continue with Painful Activities Even if They Lead to Earlier Surgery,” when to intervene with surgery may not be as intuitive as expected. The authors found that many people are willing to accommodate pain to continue a cherished activity, even if it causes harm, such as an increased risk of needing elective surgery earlier than they might otherwise [1]. The findings in this recent article are novel and can help guide patient and physician engagement in many settings.…”
mentioning
confidence: 99%
“…Amiri et al [1] found higher income was associated with greater odds of accommodating pain, continuing cherished activities, and having surgery 3 years earlier than otherwise would be the case. No such association was found for patients of lower income levels [1]. In contrast, we found in our study that patients with lower income levels were more likely to report their higher symptom level as acceptable without intervention [2].…”
mentioning
confidence: 99%
“…Reply to the Letter to the Editor: People Prefer to Continue with Painful Activities Even if They Lead to Earlier Surgery Mahsa Mohammadian Amiri MD 1 , David Ring MD, PhD 1 , Amirreza Fatehi MD 1 To the Editor,…”
mentioning
confidence: 99%